Context-based learning and its possibilities to enhance the teaching and learning of english focused on cultural identity development - Leech Morejon, Adriana Vanessa (2025)
Context-Based Learning (CBL) is a student-centred educational approach that situates language learning within real-world scenarios, integrating both social and cultural contexts, and enhancing the relevance and practicality of the knowledge acquired. CBL is integral to effective language teaching as it aims to connect academic content with practical real-life scenarios whilst integrating students’ cultural backgrounds, experiences, and interests. Despite this, Ecuador faces growing demands to align students' cultural realities with language learning content in hopes of improving foreign language teaching through methodologies such as CBL. However, these are usually poorly executed by most educators due to an inherent misrepresentation. Therefore, this research aimed to analyse the academic possibilities of the CBL teaching method in enriching the development of cultural identity through the teaching and learning of English. This qualitative study was conducted under the principles of the bibliographic, descriptive, and explicative modality. The sample included different databases such as Emerald Insight, ERIC, Google Libros, Google Scholar, JSTOR, Pro-Quest, ResearchGate, Science Direct, Scielo, Scopus, Wiley Online Library, and Web of Science. For this, an integrative literature review method was applied to provide a comprehensive synthesis of existing literature on the topic. The results reveal its constructivist and sociocultural bases within its methodological process. Alongside this, the activities that most aid CBL are cultural celebrations calendar activity, scenario-based problem-solving, role-playing, puzzles, and project-based learning. Lastly, the study shows the construction of a pedagogical guide using CBL as the foundational method as well as the five pedagogical activities chosen to enrich the development of cultural identity through the learning of English. Overall, the research highlights the constructivist and sociocultural foundations of CBL, highlighting key pedagogical activities that support cultural identity development in English learning and culminating in the creation of a pedagogical guide based on these principles